Tarbiyatul Aulad Fil Islam: Pemutus Mata Rantai Prilaku Menyimpang di Kalangan Remaja - Saputra, Doni (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Sexual deviance among students is a serious challenge in today's world of Education. This study aims to evaluate and detail the implementation of the book